The Effect of Communication, Motivation, and Work Environment on Employee Performance - Aisyah, Siti (INTERNATIONAL PENELITI EKONOMI, SOSIAL, DAN TEKNOLOGI, 2025)
Persada Arta Pratama Sangatta is one of the suppliers for PT. Kaltim Prima Coal (KPC) which is involved in the construction sector which is the provision and maintenance of plants (nursery) for greening in the PT. KPC Sangatta area. This study aims to determine the effect of communication, motivation, and work environment on employee performance at PT. Persada Arta Pratama in Sangatta. This study uses a descriptive approach with quantitative data, where research data is obtained from respondents' answers regarding research variables through questionnaires. The sample used is based on the population in this study, namely 36 employees at PT. Persada Arta Pratama. The analysis method used in this study is multiple linear regression and hypothesis testing. The results of the study indicate that (1) communication has a positive and significant effect on employee performance at PT. Persada Arta Pratama in Sangatta. This indicates that the better the communication, the better the employee performance. (2) Motivation has a positive and significant effect on employee performance at PT. Persada Arta Pratama in Sangatta. This indicates that the higher the motivation given, the higher the employee performance. (3) The work environment does not have a significant effect on employee performance. This means that good or bad work environment will not have a significant impact on employee performance at PT. Persada Arta Pratama in Sangatta. (4) Communication, motivation, and work environment simultaneously affect employee performance at PT. Persada Arta Pratama in Sangatta. The dominant factor in this study is communication.